Education Administration of Private School in Indonesia: Exploring Max Webber Thought on Bureaucracy - Christar Arstilo Rumbay; Deitje Adolfien Katuuk; Jeffry Sony Junus Lengkong; Viktory Nicodemus Joufree Rotty (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2021)
The administration system in Indonesia, especially speaking in an education institution, is suffering from its bureaucracy. Several works have been placed and display the fluctuation of the tension. This essay attempts to grasp Max Weber's idea concerning bureaucracy that may offer an alternative contribution to its development. As a qualitative work, this article explores Weber's secondary sources and tries to reconstruct its core and bridge it to the local context. In conclusion, Weber's rationalism in bureaucracy discourse highlights the importance of individual skills and abilities. Weber's attention falls to the anthropological approach rather than its technical issue.